2021
DOI: 10.1136/bcr-2021-242103
|View full text |Cite
|
Sign up to set email alerts
|

Is percutaneous glue injection one of the treatments for arteriovenous malformation pinna?

Abstract: Arteriovenous malformation (AVM) of the head and neck is a rare phenomenon, more so when it is an extracranial AVM like the auricle. AVMs are caused by genetic mutations. Most are probably present in the subclinical form at birth and then evolve; some may arise postnatally or during adolescence or get aggravated by precipitating factors like trauma, infection or hormonal influence like puberty or pregnancy. Once diagnosed, the feeding vessels have to be identified using radiological investigations. They are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Dingman et al reported three cases of auricular AVMs that underwent ligation of feeding arteries for various times (1, 4, and 8 times, respectively), but all patients eventually had auricular amputations 27 . It is thought that this treatment method failed due to neoangiogenesis and the formation of new collateral circulation 12,27,29 . Even if the ipsilateral PAA, STA, OA, and external carotid artery (ECA) are ligated, the lesion can obtain blood supply from the vertebral artery, internal carotid artery, thyroid cervical trunk, or even the contralateral ECA 16,27 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Dingman et al reported three cases of auricular AVMs that underwent ligation of feeding arteries for various times (1, 4, and 8 times, respectively), but all patients eventually had auricular amputations 27 . It is thought that this treatment method failed due to neoangiogenesis and the formation of new collateral circulation 12,27,29 . Even if the ipsilateral PAA, STA, OA, and external carotid artery (ECA) are ligated, the lesion can obtain blood supply from the vertebral artery, internal carotid artery, thyroid cervical trunk, or even the contralateral ECA 16,27 .…”
Section: Discussionmentioning
confidence: 99%
“…With the development of interventional radiology and superselective techniques, the endovascular treatment used alone or with surgery is becoming more and more important in the management of auricular AVMs. A variety of agents have been used in the management of auricular AVMs, including ethanol, 11,17 N–butyl cyanoacrylate (NBCA), 29,44,45 Onyx, 8,44 precipitating hydrophobic injectable liquid (PHIL), 46 polyvinyl alcohol (PVA) particles, 35 coils, 10,17,42,47 and gelatin sponge 12,48 . The characteristics, drawbacks, and clinical applications of these agents are summarized in Table 4 7,10,11,16,17,29,42,44,47–66 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations